Can we rely solely on conventional measures to estimate undernutrition among under-fives? - Dewan, Deepika; Gupta, Rajat; Kumar, Dinesh (Indian Journal of Community Health, 2015)
Background: Child under nutrition is still a public health problem adversely affecting the overall development and future productivity of children. Objectives: The main purpose of the study was to quantify the burden of undernutrition using both conventional indices of undernutrition and Composite Index of anthropometric failure (CIAF) and demonstrate the reliability of under-assessment by conventional indicators in urban setting. Methods: 250 under-five children registered with eight randomly selected anganwadi centres of urban slums of Jammu were studied. Anthropometric measurements were done using standardized tools. Length/height and weight were transformed to Z scores for both conventional indicators and CIAF using WHO Anthro software. CIAF was categorized using Svedberg classification. Results: A higher proportion of children were classified as undernourished by CIAF (73.2%). Only 26.8% children were anthropometrically normal. Stunting and underweight was observed in 42.8% and 38.8% under-fives respectively. Wasting was observed in only 20.4% of the children studied. Girls were more often stunted and underweight (65.4% and 66% respectively) while boys were more wasted (72.5%). 32.8% children would have been missed if underweight was used as a sole criterion to estimate undernutrition. Stunting Index (SI), Underweight Index (UI) and Wasting Index (WI) was 0.58, 0.53 and 0.27 respectively. Conclusions: CIAF categorized significantly higher percentage of undernourished children compared with conventional indicators. Routine anthropometric assessments in nutrition mitigation programs like ICDS should make use of CIAF for making short term and long term nutritional decisions both for individual children and for guiding policy decisions